2002
DOI: 10.1103/physrevb.66.064511
|View full text |Cite
|
Sign up to set email alerts
|

Reflection of a two-gap nature in penetration-depth measurements ofMgB2film

Abstract: The magnetic penetration depth, λ(T ), in the basal plane of a magnesium diboride (MgB2) film was measured using a two-coil mutual inductance technique at 50 kHz. This film has Tc ≃ 38 K, ∆Tc ≤ 1 K, and λ(0) ∼ 1500Å. At low temperatures, λ −2 (T ) shows a clear exponential temperature dependence, indicating s-wave superconducting order parameter symmetry. However, the data are not quantitatively well described by theory assuming a single gap. From the data fit by the full BCS calculation assuming a double gap,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 28 publications
6
34
0
1
Order By: Relevance
“…Also worth noting is that within the s ± -wave model with impurity scattering, 51 some low energy quasiparticle excitations can occur leading to a power law-like dependence, such as a density of states proportional to E 2 . The data can be reasonably well described by a twogap s-wave model, 52 which might be an appropriate starting point for a superconductor with multiple Fermi surface sheets. At very low temperatures, the change of superfluid phase stiffness with temperature is dominated by the smallest gap, with the larger gap becoming more apparent at high temperatures.…”
mentioning
confidence: 88%
“…Also worth noting is that within the s ± -wave model with impurity scattering, 51 some low energy quasiparticle excitations can occur leading to a power law-like dependence, such as a density of states proportional to E 2 . The data can be reasonably well described by a twogap s-wave model, 52 which might be an appropriate starting point for a superconductor with multiple Fermi surface sheets. At very low temperatures, the change of superfluid phase stiffness with temperature is dominated by the smallest gap, with the larger gap becoming more apparent at high temperatures.…”
mentioning
confidence: 88%
“…For instance, both bands are known to play an important role in determining the specific heat of MgB 2 6,7 , and explaining anomalous temperature-dependent anisotropy of the upper critical field 8,9 . Meanwhile Kim et al reported that the measured penetration depth (λ) of MgB 2 is mainly due to the role of the σ-band 10 . Recently, other interesting results have been reported with regard to the microwave conductivity of MgB 2 by Jin et al…”
Section: Introductionmentioning
confidence: 99%
“…There are currently many indications that the recently discovered MgB 2 superconductor [17] can be described by the classical two-gap model [20,21] which convincingly fits the specific heat [22] and penetration depth measurements [23]. In particular, in [24,25,26] even the values of the coupling constants for the system of equations (22) for the two-gap and two-band model of MgB 2 were given.…”
Section: Implications For Mgb2mentioning
confidence: 99%
“…To consider neutral superconductor one can formally set e = 0 in (23), so that the terms with the electric potential ϕ disappear from the equations and we arrive at…”
Section: Collective Excitations In a Neutral Superconductormentioning
confidence: 99%